P86 Does genotype predict response to treatment in children perinatally infected with hepatitis B virus. (16th November 2010) - Sira, J; Boxall, E; Kaskar, S; Workman, J; Kelly, D
Abstract : Introduction: Hepatitis B Virus (HBV) genotype is now thought to correlate to outcome and response to treatment. Aim: To compare viral genotype with treatment response in children infected perinatally with HBV, who had been treated with subcutaneous Interferon alpha2b (IFN) with or without Prednisolone priming (Pred/IFN), oral antiviral drugs (Lamivudine or Adefovir). Method: All children who took part in the clinical trials in this unit since 1990 were included. The hepatitis B genotypes were determined using a commercial line probe assay (InnoLipa), which was validated against direct sequencing. Results: 70 children were recruited to clinical trials, 68 of whom had genotype analysis. 5 children had more than one course of therapy: The genotype results correlated with the geographical origin of the families of the children. European and Afro-Caribbean children have genotype A, Oriental children only had genotype B, while the majority of South Asian children had genotype D. Genotype C was uncommon in any of these ethnic groups. Overall response to treatment was better in children with genotypes A 10/18 (55%) and D 19/39 (49%) compared to those with B and C for all forms of treatment. Although the response to Interferon alone was better in children with genotype A (50%) compared to D (36%), prednisolone priming improved the response in both genotypes to 67% & 70% respectively. Conclusion: Pre-treatment assessment of genotype in children may provide a guide to potential response and improve information and choice for families. Abstract P86 Table 1 Results: Seroconversion by treatment and genotype Number A B C D (%) (%) (%) (%) Trial 1 Pred/IFN 19 4/6 (67) 0/2 0/1 7/10 (70) IFN 20 2/4 (50) 0/5 0 4/11 (36) Trial 2 Lamivudine 22 2/5 (40) 0/1 0/1 8/15 (53) Trial 3 Adefovir 7 2/3 (67) 0 0/1 0/3